At udtage én - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 1995)
The rite of the laying on of hands in the Hebrew Bible has been interpreted in different ways, with no final conclusion being arrived at until now. Despite the ritual and semantic diversities of the different instances, one common point unites them all: in all instances one member is singled out of an anonymous group (or a group is singled out of a bigger group). The rituals to which the laying on of hands belongs can lead to enhanced life or death, to honour or shame, to an existence at the centre of the community or outside it. The rite belongs to a bigger group of rites which encompasses the drawing of lots, anointment and stoning and which forms a transformational system.